2002
DOI: 10.4319/lo.2002.47.5.1283
|View full text |Cite
|
Sign up to set email alerts
|

Colored dissolved organic matter and dissolved organic carbon exclusion from lake ice: Implications for irradiance transmission and carbon cycling

Abstract: Thick ice cover is a feature of cold-temperate, polar, and alpine lakes and rivers throughout much of the year. Our observations from Canadian lakes and rivers across the latitudinal gradient 46-80ЊN show that their overlying ice contains low concentrations of dissolved organic carbon (DOC) and colored dissolved organic matter (CDOM) relative to the underlying waters. The CDOM exclusion factor (water/ice) ranged from 1.4 to 114 and was typically greater than twice the exclusion factor for inorganic solutes. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 43 publications
(61 reference statements)
8
134
1
Order By: Relevance
“…Warmer winters will result in a shortening of the period with snow and ice cover. The importance of wintertime climatic control on DOC dynamics in lakes has already been identified by Belzile et al (2002), Park et al (2005), Karlsson et al (2008), and. From these studies, DOC concentrations are expected to increase along with warmer winters.…”
Section: Discussionmentioning
confidence: 99%
“…Warmer winters will result in a shortening of the period with snow and ice cover. The importance of wintertime climatic control on DOC dynamics in lakes has already been identified by Belzile et al (2002), Park et al (2005), Karlsson et al (2008), and. From these studies, DOC concentrations are expected to increase along with warmer winters.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Belzile et al (2002) demonstrated that the exclusion factor for natural organic matter from Canadian lakes is typically greater than twice the exclusion factor for inorganic solutes. Only lesscomplex, low-molecular-weight molecules were retained in the ice.…”
Section: Resultsmentioning
confidence: 99%
“…The slopes of FDOM P concentrations against DOC concentrations varied significantly over different seasons, with steeper gradients in the spring (March and April) and fall (October). In general, FDOM P is known to be produced efficiently by biological production in water (Coble, 1996;Belzile et al, 2002;Steinberg et al, 2004;Zhao et al, 2017). Thus, higher FDOM P concentrations relative to DOC concentrations in the spring and fall seem to be associated with the spring and fall phytoplankton blooms in river waters (Mayer et al, 1999;Zhang et al, 2009).…”
Section: Behaviors and Sources Of Fdom In The Estuarine Mixing Zonementioning
confidence: 99%